Pengaruh Lingkungan Kerja, Gaya Kepemimpinan Kepala Sekolah, dan Budaya Organisasi Terhadap Kepuasan Kerja Guru di SMPN 1 Pule Trenggalek - Bekti, Tata Sastya; Adji, Setyo; Rapini, Titi (JURNAL ADMINISTRASI KANTOR; Vol 12 No 1 (2024): Jurnal Administrasi Kantor (Juni 2024), 2024)
Although education can be obtained in various places, the best institution to obtain it is school, with teachers as the main source of knowledge. This research aims to find out whether elements such as the work environment, the principal's leadership style, and organizational culture influence the level of teacher job satisfaction at SMPN 1 Pule Trenggalek. This research uses quantitative methods with data analysis carried out using the Statistical Package for the Social Sciences (SPSS) software. The respondents for this research involved all teachers, both ASN/PPPK and non-ASN/PPPK, totaling 46 people. Data collection was carried out using a questionnaire, and analysis used multiple linear regression. The research results show that the teacher's work environment has a positive influence on teacher job satisfaction, where the Tcount value (2.125) is greater than Ttable (2.018) and the significance value of 0.040 is greater than 0.05. However, the principal's leadership style does not have a significant positive influence on job satisfaction, this is indicated by the Tcount value (-0.127) being smaller than Ttable (2.018) and the significance value (0.899) being greater than 0.05. Overall, this research reveals that the work environment and organizational culture jointly influence teacher job satisfaction at SMPN 1 Pule Trenggalek, while the principal's leadership style does not have a significant influence on teacher job satisfaction.   Keywords : Work Environment, Leadership Style, Organizational Culture, Job Satisfaction